The Politics of Irony against Dehumanization in Coetzee’s Novel, Waiting for the Barbarians - Sapkota, Tikaram (Lumbini Journal of Language and Literature, 2026)
This paper has examined the role of irony in Coetzee’s post modern novel, Waiting for the Barbarians as the primary data, focusing on its role in critiquing the dehumanizing aspects of colonial apartheid South Africa during the 1970s and 1980s. Employing the qualitative literary analysis methods and discursive research design, the study has used irony as a political tool to expose and challenge the oppressive and exploitative nature of the apartheid regime from the perspective of its marginalized victims. Based on interpretivist approach and drawing on the theory of the politics of irony, the analysis demonstrates how Coetzee foregrounds the suffering and predicament of Black South Africans to denounce torture, violence, and systemic injustice. The novel thus calls for a transformation in the way people perceive and treat one another, urging a more humanistic view of humanity. The paper concluded that through the character of the white colonial agent and narrator, who ultimately sides with the subalterns, the narrative enacts a politics of irony that powerfully critiques the cruelty and brutality of apartheid while advocating for the rights, dignity, equality, and inclusion of the marginalized.